Multi-Scale evaluation of low-temperature performance in asphalt mixtures using not-notched semi-circular bending creep testing - Xi, Xinghao; Tang, Dong; Wang, Zhenghe; Zhang, Naitian (Frontiers in Materials, 2025)
To address the challenge of obtaining core samples directly from the field for low-temperature crack resistance tests of asphalt mixtures, this study utilizes the not-notched semi-circular bending (NN-SCB) creep test as a novel evaluation method. The feasibility of this method is discussed and validated through both simulation and experimental testing. First, ABAQUS software was employed to model the NN-SCB creep test, with various viscoelastic and creep load parameters analyzed to evaluate the percentage of tensile creep dissipation energy in asphalt mixtures with different characteristics. The results indicate that the tensile creep dissipation energy consistently accounts for approximately 31.5% of the total creep dissipation energy across all tested asphalt mixtures, irrespective of their properties. Five types of asphalt mixtures were designed, three of which incorporated Reclaimed Asphalt Pavement (RAP) as the aggregate base. These mixtures were subjected to both NN-SCB and Thermal Stress Restrained Specimen Test (TSRST) methods. The experimental findings demonstrate that the tensile creep dissipation energy in the NN-SCB test provides a robust and consistent measure of low-temperature crack resistance, with results closely aligning with those from TSRST. Specifically, the tensile creep dissipation energy of mixtures containing 40% RAP showed a significant reduction in low-temperature cracking resistance, with a 41.3% lower creep rate compared to the virgin asphalt mixture. The study confirms the feasibility of using NN-SCB and tensile creep dissipation energy as reliable indices for evaluating the low-temperature crack resistance of asphalt mixtures.